2014
DOI: 10.1080/00028487.2013.852623
|View full text |Cite
|
Sign up to set email alerts
|

Effectiveness of Instream Wood Treatments to Restore Stream Complexity and Winter Rearing Habitat for Juvenile Coho Salmon

Abstract: Large wood and boulder placement projects have become common in the Pacific Northwest to restore complex stream habitat for juvenile Coho Salmon Oncorhynchus kisutch and other salmonids. We evaluated habitat responses at 91 large wood restoration projects in western Oregon from pretreatment to 1 year and 6 years after treatment. Large logs were arranged in jams without cabling or burial in the bottom or banks of the stream. Projects commonly treated 0.5–1 km of stream, but some extended up to 2.3 km. Significa… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

1
31
0

Year Published

2015
2015
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 37 publications
(32 citation statements)
references
References 36 publications
1
31
0
Order By: Relevance
“…() and Jones et al . () review some of these restoration projects and the success of the projects in achieving desired restoration of fish habitat and the return of stream channels to a more natural state.…”
Section: Discussionmentioning
confidence: 97%
“…() and Jones et al . () review some of these restoration projects and the success of the projects in achieving desired restoration of fish habitat and the return of stream channels to a more natural state.…”
Section: Discussionmentioning
confidence: 97%
“…A major goal of wood placement in streams and rivers is to improve physical habitat such as increasing pool area, habitat complexity, instream cover, and other metrics of fish-habitat quality. These changes are also linked to the amount or intensity of treatment, as there is a strong positive correlation between amount of wood and both physical habitat quality and fish numbers for both natural (Beechie et al 2005;Murphy et al 1984;Naiman et al 2002) and placed wood (Jones et al 2014;Roni and Quinn 2001a). Thus, if the placed wood or wood structures remain on site or function as designed, there typically are significant improvements in habitat.…”
Section: Physical Response To Wood Placementmentioning
confidence: 99%
“…Improvements in physical habitat following wood placement, including increased pool area, cover, and habitat complexity (number and diversity of habitats), have been well documented (Jones et al 2014;Roni et al 2008). In fact, many studies report large (>50%) and significant increases in pool frequency, pool depth, woody debris, habitat heterogeneity, complexity, spawning gravel, or sediment and organic matter retention following placement of instream structures, particularly in mountain streams and rivers (e.g., Binns 1999; Brooks et al 2004;Cederholm et al 1997;Gerhard and Reich 2000;Pierce et al 2013;Reeves et al 1997;Roni and Quinn 2001a).…”
Section: Physical Response To Wood Placementmentioning
confidence: 99%
See 1 more Smart Citation
“…A few meta-analysis studies have compared compendiums of past projects and results from monitoring individual habitat enhancement projects to help determine effectiveness (Avery 2004;Binns 2004;Whiteway et al 2010), but these studies primarily focused on instream structures, and in some (e.g., Stewart et al 2009) the results were equivocal. While several agencies fund large state or federal restoration programs, few studies have reported on a comprehensive programmatic evaluation of any large restoration program (e.g., Jones et al 2014); specifically lacking are studies across a large area, monitoring multiple project types, and using consistent protocols. Many of these agencies have only recently implemented or are currently trying to implement comprehensive monitoring programs on restoration effectiveness so evaluation of this type of work is timely.…”
mentioning
confidence: 99%